(untitled) (Zoo Botanica, 2025)
Sesame (Creontiades dilutus) is a traditionally important crop and is well-known as the "queen of oilseeds". Sesame seeds contained 18-25% protein, 44-57% oil and 13-14% carbohydrates. Mirid bug is considered as major pest of the sesame. In current study, seven treatments, viz. Nitenpyrum 25%SP, Acephate 97DF, Dimethoate 40% EC, Flunicamid 50% DF, Chlorfenapyr 360SC, Fipronil 80WG, Chlorantraniliprole 20SC were applied on mirid bug present on sesame at Research Farm Area of Entomological Research Institute Faisalabad during Kharif 2023-24 at recommended doses. The application of above said treatments on sesame crop was done at ETL population of mirid bug. Pretreatment data and percent reduction was recorded after 3 and 7 days after application of treatments. The results revealed that maximum percentage reduction in mirid bug population was recorded in plots treated with nitenpyram 25%SP 84% and 85% during 2023-24 respectively. However, chlorfenapyr 360SC and dimethoate 40%EC observed 81.84 and 81.05 percentage population reduction alternatively, while chlorantraniliprole 20SC showed the lowest population reduction during both years. These findings emphasize the importance of integrating multiple control options within IPM frameworks to sustain effective pest control and reduce the risk of resistance development. Continuous monitoring and further research are essential to assess environmental impact and the potential of combining chemical and non-chemical methods for sustainable sesame production